Non-linear association of sleep duration with osteoarthritis among middle-aged and older adults: Results from a prospective cohort study in China - Long Long; Qi Wang; Bohao Fang; Li Cao; Yingjie Xu; Guangyang Li (PLoS ONE, 2025)
Background The association between nighttime sleep duration and osteoarthritis (OA) remains ambiguous. Chinese older adults exhibit distinct sleep patterns, as well as genetic predispositions and rapidly changing lifestyles, which may have shaped the unique epidemiology of OA. However, most existing evidence is based on Western populations. This study aimed to investigate this association and the potential moderating role of BMI in middle-aged and older Chinese adults. Methods Data of wave 1 (2011) and wave 4 (2018) were obtained from the nationally representative China Health and Retirement Longitudinal Study (CHARLS). Univariate and multivariate logistic regression models were utilized to explore the association of sleep duration and OA with sleeping 7–9 h as reference group. Additionally, to further explore the potential combined effect of sleep and BMI, interaction terms were added into the model. Restricted cubic spline was also used to explore the non-linear correlation between sleep duration and OA. Results Out of 6,825 participants, 1,396 were diagnosed with OA. After multivariable adjustment, the odds ratios (OR) for OA were 1.39 (95% CI 1.20–1.60; P < 0.001) for individuals with sleep duration (<6 h/night) and 1.27 (95% CI 1.20–1.60 P = 0.003) for individuals with sleep duration (6–7 h/night). The association between sleep duration and OA followed a U-shaped pattern, with 7.5 h acting as an inflection point. Significant interactions were found in overweight individuals, with both short (OR = 1.41, P = 0.042) and long (OR = 2.71, P = 0.006) sleep durations increasing OA risk. Conclusions Short sleep duration (<7h) was associated with a higher incidence of OA. A U-shaped association was observed between sleep duration and OA incidence among middle-aged and older Chinese adults. BMI may act as a moderator in this relationship.